Persistence of Inflammatory Phenotype in Residual Psoriatic Plaques in Patients on Effective Biologic Therapy - Mashiko, Shunya; Edelmayer, Rebecca M.; Bi, Yingtao; Olson, Lauren M.; Wetter, Joseph B.; Wang, Jing; Maari, Catherine; Saint-Cyr Proulx, Etienne; Kaimal, Vivek; Li, Xuan; Salte, Katherine; Garcet, Sandra; et al. (Journal of investigative dermatology, 2020)
Many psoriasis patients treated with biologics do not achieve total skin clearance. These patients possess residual plaques despite ongoing biologic treatment. To elucidate mechanisms of plaque persistence despite overall good drug response, we studied 50 subjects: psoriasis patients with residual plaques treated with one of three different biologics, untreated patients, and healthy controls. Skin biopsies from all subjects were characterized using three methods: mRNA expression, histology, and FACS of hematopoietic skin cells. Although all three methods provided evidence of drug effect, gene expression analysis revealed the persistence of key psoriasis pathways in treated plaques, including granulocyte adhesion and diapedesis, T helper type17 activation pathway, and interferon signaling with no novel pathways emerging. Focal decreases in parakeratosis and keratinocyte proliferation and differential reduction in IL-17 producing CD103– T cells, but no change in CD103+ tissue-resident memory T cells were observed. Of note, antitumor necrosis factor increased the interferon signaling pathway already present. Interestingly mast cells were the dominant source of IL-22 in all psoriasis subjects. These data suggest that while subtle differences can be observed in drug-treated plaques, underlying biologic mechanisms are similar to those present in untreated psoriatic lesions.